Photoresponsive and wetting performances of sheet-like nanostructures of tungsten trioxide thin films grown on wood surfaces. Issue 90 (1st October 2015) - Hui, Bin; Wu, Dianxiu; Huang, Qiongtao; Cai, Liping; Li, Guoliang; Li, Jian; Zhao, Guiling
<x xml:space="preserve">Abstract</x> Tungsten trioxide films with sheet-like nanostructures coated on wood substrates possessed photoresponsive behavior and superhydrophobic performance after OTS treatment.